Synchronous comparison in the research of the history of state and law phenomena (at the example of Justices of the Peace institution created in the Russian Empire in 1864) - Шигаль, Д. А. (Theory and practice of jurisprudence, 2016)
In this article the specific of synchronous historical comparison is researched at the example of the institution of Justices of the Peace, which was created in 1864. The stipulations of the applying of this method are analyzed. The inferences have been made about significance of historical-synchronous analysis in the sphere of studying the history of state and law phenomena.